The Influence of Financial Literacy on Entrepreneurial Behavior Among University Students - Bravo Philip Ayebare (Uganda Christian University, 2023)
Financial literacy has been recognized as a crucial factor in poverty reduction and enhancing employability rates. However, there is a scarcity of empirical evidence on the specific mechanisms through which financial literacy influences entrepreneurial behavior, particularly among university students. Despite the recognized importance of financial literacy in poverty reduction and enhanced employability rates, there is limited empirical evidence on the underlying mechanisms of change in the context of entrepreneurial behavior. To address this gap, the study explores the influence of financial literacy on entrepreneurial behavior, while also examining potential variations in this relationship based on gender and socioeconomic status. The study adopted a mixed research approach, utilizing primary data collected through structured surveys distributed to a diverse sample of students at Uganda Christian University. The survey included questions related to financial literacy, entrepreneurial behavior, financial capability, gender, and socioeconomic status. Data was analyzed using appropriate statistical methods that are correlation and regression analysis, to examine the relationships between the variables and identify potential differences based on gender and socioeconomic status. The study found that participants had average financial literacy, with room for growth in understanding specific financial products and services. Although there was a significant tendency towards entrepreneurship, practical involvement and training in entrepreneurial activity differed. The study discovered a positive relationship between financial literacy and entrepreneurial behavior, emphasizing the importance of financial knowledge, decision-making abilities, and awareness of financial products and services in generating entrepreneurial aspirations. Gender and socioeconomic status were investigated as potential moderating factors, and while some connections were detected, they were not consistently strong or statistically significant across all variables. This study emphasizes the significance of focused interventions to increase financial literacy and practical engagement, notably through integrated curriculum creation, experiential learning, mentorship, resource centers, public awareness campaigns, and longitudinal studies. Finally, this study adds to our understanding of the relationship between financial literacy and entrepreneurial behavior among university students. Academic institutions may equip students to manage the difficulties of entrepreneurship with confidence by encouraging financial literacy and an entrepreneurial mindset, ultimately contributing to economic growth and development. Future study ideas include longitudinal investigations, comparative assessments, intervention evaluations, and cultural factors.
This is a dissertation.